2018
DOI: 10.18332/tid/99881
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptual Model and Methods of Wave 1 ( 2016 ) of the EUREST-PLUS ITC 6 European Countries Survey

Abstract: Population-level interventions represent the only real approach for combatting the tobacco epidemic. There is thus great importance in conducting rigorous evaluation studies of tobacco control policies and regulations such as those arising from the WHO Framework Convention on Tobacco Control (FCTC) and the European Union’s 2014 Tobacco Products Directive (TPD). The ITC 6 European Countries Survey, a component of the Horizon 2020 Project entitled European Regulatory Science on Tobacco: Policy Implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 26 publications
(23 reference statements)
0
41
0
Order By: Relevance
“…Interviews were conducted face-to-face using computer assisted personal interviews (CAPI). Further details about the study methodology are provided elsewhere [ 20 , 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews were conducted face-to-face using computer assisted personal interviews (CAPI). Further details about the study methodology are provided elsewhere [ 20 , 21 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Demographic characteristics examined were age (18–24, 25–39, 40–54 and ≥55 years); gender (male, female); degree of urbanisation (urban, intermediate, rural); highest level of formal education completed (low, moderate, and high); monthly gross household income (low, moderate and high) [ 20 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…itcproject.org/). This cohort survey (ITC 6E Survey) follows the methods of the ITC Project, explained in detail elsewhere 6,7 . Briefly, samples of adult (≥18 years old) current smokers (having smoked >100 cigarettes in their lifetimes and having smoked at least once in the past 30 days) were recruited by probability sampling methods, being representative of all geographical regions in each country.…”
Section: Methodsmentioning
confidence: 99%
“…This sample was aged 43.2 (SE=0.19) years on average, 43.5% female, and 14.0% had higher education (for a detailed description of the sample, including the breakdown of prevalence of smoking of different cigarette flavours across sociodemographic groups and countries, see Zatoński et al 13 in the same supplement). The ITC 6E Survey was conducted between 18 June 2016 and 12 September 2016 12,28 . The surveyed sample comprised a nationally representative sample of adult cigarette smokers aged ≥18 years (about 1000 participants in each country).…”
Section: Sampled Populationsmentioning
confidence: 99%
“…To date, most studies of menthol cigarette smokers have been conducted in the United States [4][5][6][7][8][9][10] , with little research available on European smokers 11 . The International Tobacco Control (ITC) Project conducted in eight European countries offers an opportunity to study the characteristics and behaviours of MFC smokers 12 . An earlier study using this sample has shown important differences in the prevalence of flavoured cigarette use between different European countries, as well as considerable differences in attitudes towards tobacco control policies between users of different cigarette flavours 13 .…”
Section: Introductionmentioning
confidence: 99%